The Association Between Pro-Inflammatory Cytokines and Antiretroviral Therapy Resistance-Related Mutations in HIVPositive Patients - Dwitya Elvira; Rizka Nadia; Raveinal Raveinal (Turkish Journal of Immunology)
Objective: Human-immunodeficiency virus (HIV) infection initiates the dysregulated production of pro-inflammatory cytokines. Moreover, unsuccessful treatment for HIV might be due to the drug resistance mutations (DRM) against anti-retroviral therapy (ART). This study aimed to compare pro-inflammatory cytokines levels of HIV patients, who received first line ART and patients, with mutations of M184V and K103N. Materials and Methods: This was a case-control study which involved eighty patients with AIDS who received first-line anti-retroviral therapy for at least 6 months. The respondents were divided into two groups of patients with HIV with DRM and the ones with HIV without DRM. M184V and K103N drug resistance mutations to ART were analyzed using reverse transcription-polymerase chain reaction (RT-PCR) meanwhile tumour necrosis factor alpha (TNF-α) and interleukin (IL)-6 as pro-inflammatory cytokines were measured using enzyme linked immunosorbent assay. Results: Most of the patients were men with an average age of 35.5 +- 9.2 years. The median levels for TNF-α and IL-6 were found 43.3 (4.3-96.1) pg/mL and 46.2 (15.5-158.1) pg/mL, respectively. The results showed that the DRM group got higher values compared to the non-DRM group, but there was no statistically significant difference found between both groups. Conclusion: There were no differences in pro-inflammatory cytokines between the DRM AIDS patients group compared to the non-DRM who received first-line ART with mutations of M184V and K103N.